The role of health animators in malaria control: a qualitative study of the health animator (HA) approach within the Majete malaria project (MMP) in Chikwawa District, Malawi - Kaunda-Khangamwa, Blessings N. (BMC Health Serv Res, 2019)
BACKGROUND: Malaria continues to place a high burden on communities due to challenges reaching intervention target levels in Chikwawa District, Malawi. The Hunger Project Malawi is using a health animator approach (HA) to address gaps in malaria control coverage. We explored the influence of community-based volunteers known as health animators (HAs) in malaria control. We assessed the impact of HAs on knowledge, attitudes, and practices towards malaria interventions. METHODS: This paper draws on the qualitative data collected to explore the roles of communities, HAs and formal health workers attending and not attending malaria workshops for malaria control. Purposive sampling was used to select 78 respondents. We conducted 10 separate focus group discussions (FGDs)-(n = 6) with community members and (n = 4) key informants. Nine in-depth interviews (IDIs) were held with HAs and Health Surveillance Assistants (HSAs) in three focal areas near Majete Wildlife Reserve. Nvivo 11 was used for coding and analysis. We employed the framework analysis and social capital theory to determine how the intervention influenced health and social outcomes. RESULTS: Using education, feedback sessions and advocacy in malaria workshop had mixed outcomes. There was a high awareness of community participation and comprehensive knowledge of the HA approach as key to malaria control. HAs were identified as playing a complementary role in malaria intervention. Community members’ attitudes towards advocacy for better health services were poor. Attendance in malaria workshops was sporadic towards the final year of the intervention. Respondents mentioned positive attitudes and practices on net usage for prevention and prompt health-seeking behaviours. CONCLUSION: The HA approach is a useful strategy for complementing malaria prevention strategies in rural communities and improving practices for health-seeking behaviour. Various factors influence HAs’ motivation, retention, community engagement, and programme sustainability. However, little is known about how these factors interact to influence volunteers’ motivation, community participation and sustainability over time. More research is needed to explore the acceptability of an HA approach and the impact on malaria control in other rural communities in Malawi.